(untitled) (Swiss Medical Weekly, 2025)
AIMS: The literature from Canada, the UK and the USA reports health inequities among people experiencing homelessness; however little is known about this population’s health in Switzerland. Our study is the first to comprehensively assess health needs, expectations and experiences of people experiencing homelessness in Switzerland. METHODS: We describe the health needs, expectations and experiences of people experiencing homelessness in French-speaking Switzerland, using both quantitative and qualitative methods. From May to August 2022, 123 people experiencing homelessness completed quantitative questionnaires about health needs, expectations and experiences. Recruitment took place in 10 homeless-serving institutions across four cities in the Canton of Vaud. A total of 18 people experiencing homelessness and 13 professionals involved in the homeless-serving sector completed qualitative interviews. For the qualitative strand, we selected people experiencing homelessness using quota sampling based on health insurance, residency status and sex representativeness according to the study population. For homeless-serving sector professionals, we used quota sampling by professions (i.e. night watcher in shelters; social/healthcare workers) ensuring balance. In addition, we aimed to recruit at least one homeless-serving sector professional from each of the ten institutions included in the parent research project. RESULTS: The most common health issues reported were musculoskeletal, dental and psychiatric. Thirty-one percent of people experiencing homelessness had visited emergency rooms and 27% a community health centre in the prior 6 months. People experiencing homelessness reported low quality of life according to the WHOQOL, especially in social and environmental domains; 33% reported moderate and 17% high grade of psychological distress. Findings indicated that up to 32% of participants reported facing difficulties in reaching out to the healthcare system. In qualitative interviews, people experiencing homelessness described positive perceptions about the Swiss healthcare system. However, people experiencing homelessness reported various barriers encountered while seeking healthcare (e.g., health insurance, financial barriers, appointment delays, hesitancy in accessing care, prioritising other needs). Both groups commonly reported that social situations impacted the health and healthcare use of people experiencing homelessness. CONCLUSION: People experiencing homelessness in Switzerland are not spared by the common health inequities reported in Canada, the USA and the UK. Our results provide interesting foundations on which to build public health actions towards health equity for people experiencing homelessness in Switzerland and suggest that they could benefit from additional medical follow-up and tailored interventions.